Dynamics in oral health‐related factors of Indigenous Australian children: A network analysis of a randomized controlled trial. Issue 4 (28th May 2021) - Soares, Gustavo Hermes; Ribeiro Santiago, Pedro Henrique; Biazevic, Maria Gabriela Haye; Michel‐Crosato, Edgard; Jamieson, Lisa
Abstract: Objectives: Network analysis is an innovative, analytic approach that enables visual representation of variables as nodes and their corresponding statistical associations as edges. It also provides a new way of framing oral health‐related questions as complex systems of variables. We aimed to generate networks of oral health variables using epidemiological data of Indigenous children, and to compare network structures of oral health variables among participants who received immediate or delayed delivery of an oral health intervention. Methods: Epidemiological data from 448 mother‐child dyads enrolled in a randomized controlled trial of dental caries prevention in South Australia, Australia, were obtained. Networks were estimated with nodes representing study variables and edges representing partial correlation coefficients between variables. Data included dental caries, impact on quality of life, self‐rated general health, self‐rated oral health, dental service utilization, knowledge of oral health, fatalism and self‐efficacy in three time points. Communities of nodes, centrality, clustering coefficient and network stability were estimated. Results: The oral health intervention interacted with the network through self‐rated general health and knowledge of oral health. Networks depicting groups shortly after receiving the intervention presented higher clustering coefficients and a similar arrangement of nodes. Networks tended to return to a preintervention state. Conclusion: The intervention resulted in increased connectivity and changes in the structure of communities of variables in both intervention groups. Our findings contribute to elucidating dynamics between variables depicting oral health networks over time.